The impact of halal certification compliance on organizational performance in SME halal food company: the role of religiosity as moderating variable - Sitti Aminah, Baharuddin (2020)
The halal industry contributes to economic growth through an increased demand for halal products that are certified halal. This is due to the confidence given by the halal certification to consumers. In Malaysia, halal certification is seen as a marketing method for food producers. However, there is still a certain level of failure in the industry in maintaining halal certification due to the issue of noncompliance notices. More than 9 cases were reported due to non-compliance notices on halal certification involving Small and Medium Enterprises (SMEs). In Malaysia halal certification is optional, and it is up to the top management to decide whether to implement the certification. Meanwhile, religion is one of the factors that influence the decision in maintaining halal certification standards. In this study, the researchers examined the impact of halal certification compliance on organizational performance, and religion as a moderation variable. Data were collected using survey methods through the distribution of structured questionnaires to SME halal food producers in Malaysia. In this study, Partial Least Square (PLS) was used to test the model. The results of the study show that compliance with halal certification affects the performance of the organization while religious factors, as a moderation variable, do not moderate the relationship. The results of this study also found remarkable findings where halal certification applicants take advantage of this opportunity to thrive in the halal market. The main limitation of this study was the small number of respondents. Future research should broaden the scope of this study by expanding it to other sectors such as the cosmetics and pharmaceutical industries, to enhance the generalization of research results.